Comparative efficacy and safety of various Chinese patent medicines combined with western medicine for adults with insomnia: A Bayesian network meta-analysis of randomized controlled trials - Ciyan Peng; Jing Chen; Sini Li; Boyin Huang; Wei Cui; Jianhe Li; Liubao Peng (Pharmacological Research - Modern Chinese Medicine, 2023)
Background: Considering the limitations of Western medicine (WM) in treating Insomnia among adults, and the extensive use of Chinese patent medicines (CPMs), a comprehensive evaluation of the efficacy and safety of Different CPMs used in combination with WM for Insomnia in adults is necessary. To this end, a systematic investigation was conducted to scrutinize the effectiveness and safety of using 16 different CPMs in conjunction with WM in treating Insomnia in adults. The present study employed a network meta-analysis technique to compare and evaluate the combined therapeutic potential of these 16 CPMs and WM in treating adults with Insomnia. Methods: Literary databases were scrupulously combed through from their commencement until November 2022 to collect all randomized controlled trials (RCTs) that centered on adult patients afflicted with insomnia and treated with a blend of Chinese patent medicines (CPMs) and Western medicine (WM). The investigation analyzed diverse outcomes, comprising total effective rate, Pittsburgh sleep quality index (PSQI), occurrence of somnolence, occurrence of dry mouth, and occurrence of dizziness. The examination utilized advanced statistical tools such as RevMan (5.3), Stata/MP17, and R software, and also calculated the surface under the cumulative ranking curve (SUCRA) probability values, which were employed to rank the examined treatments. In addition, the inquiry executed clustering analysis to contrast the effects and safety of CPMs on distinct outcomes. Results: A total of 283studies involving 27,151patients and 16 CMPs were included. The 16 CMPs were: Wulingjiaonang (WLJN), Anshenbunaoye (ASBNY), Baileminjiaonang (BLWJN), Shenqiwuweizi (SQWWZ), Shensongyangxinjiaonang (SSYXJN), Jiaotaiwan (JTW), Yangxinanshengwan (YXASW), Tianwangbuxindan (TWBXD), Zhushaanshenwan (ZSASW), Yangdanxinnaotong (YDXNT), Yangxueqingnaokeli (YXQNKL), Tianmengjiaonang (TMJN), Zaorenanshenjiaonang (ZRASJN), Shuganjieyujiaonang (SGJYJN), Xiaoyaosan (XYS), Shumianjiaonang (SMJN). The results of the network meta-analysis showed that, with WM treatment as a co-intervention, SSYXJN was most likely to improve the total efficiency rate (SUCRA= 84.70%), ASBNY had the highest probability of being the best option for improving the Sleep quality (SUCRA= 99.20%), JTW had the highest probability of reducing the incidence of somnolence (SUCRA= 94.10%), ZSASW had the highest probability of reducing the incidence of dry mouth (SUCRA= 74.70%), while WLJN had the highest probability of reducing the incidence of dizziness (SUCRA= 73.10%). Conclusions: CPMs combined with WM is proved to be more effective and safer than WM alone, which may be beneficial to adults with Insomnia patients. SQWWZ+WM(Level of evidence, moderate) and ZSASW+WM(Level of evidence, moderate) are most likely the optimal CPM to improve total efficiency rates, Sleep quality, and reduce adverse effects. This study, however, has some limitations as discussed in this article; therefore, higher quality RCTs and real-world evidence are required to support our conclusions.